Applications in Electronics Pervading Industry, Environment and Society APPLEPIES 2014 - De Gloria, Alessandro (Lecture Notes in Electrical Engineering,, 2016)
This book provides a thorough overview of cutting-edge research on electronics applications relevant to industry, the environment, and society at large. A wide spectrum of application domains are covered, from automotive to space and from health to security, and special attention is devoted to the use of embedded devices and sensors for imaging, communication, and control. The book is based on the 2014 APPLEPIES Conference, held in Rome, which brought together researchers and stakeholders to consider the most significant current trends in the field of applied electronics and to debate visions for the future. Areas covered by the conference included information communication technology; biotechnology and biomedical imaging; space; secure, clean, and efficient energy; the environment; and smart, green, and integrated transport. As electronics technology continues to develop apace, constantly meeting previously unthinkable targets, further attention needs to be directed toward the electronics applications and the development of systems that facilitate human activities. This book, written by industrial and academic professionals, will hopefully contribute in this endeavor.